Evolution of scientific approaches to detecting the causes of destructive processes within the organizational and technological system of construction - MALYKHIN, Mykhailo (Ways to Improve Construction Efficiency, 2025)
Construction is one of the most complex and risky areas of economic activity, where numerous technological, organizational, economic and social factors are combined. In such conditions, the occurrence of destructive processes is inevitable, but the effectiveness of the industry depends on the ability to detect, analyze and neutralize them in a timely manner. Destructive phenomena manifest themselves in the form of planning failures, incoherence of participants’ actions, overspending of resources, technological violations and a decrease in the quality of the final result. Their nature is systemic, which requires an interdisciplinary approach to diagnostics and management. Scientific approaches to the study of the causes of destruction in construction production have undergone significant evolution – from intuitive and descriptive methods to analytical and digitally-oriented management models. If in the past attention was paid mainly to economic and technical aspects of efficiency, now the issues of system management of stability, adaptability and digital interaction of components of the organizational and technological structure are gaining increasing importance. Digitalization technologies play a significant role in the development of modern methods of analyzing destructive processes – in particular, BIM, ERP, CRM and Big Data Analytics systems. They create the opportunity not only to record deviations, but also to predict their occurrence by analyzing accumulated data in real time. Static models have been replaced by cognitive and analytical systems capable of self-learning and adaptation, which significantly increases the accuracy of management decisions. The study focuses on the need to transition from reactive strategies to predictive and analytical management, when the causes of destruction are determined not after the fact, but in the process of forming management decisions. It was found that the key factors of destructive processes are insufficient integration of information systems, organizational inertia, lack of managerial competencies and the absence of a unified methodology for assessing the sustainability of production systems. A conceptual model is proposed in which construction production is considered as an open system that constantly interacts with a dynamic external environment. This approach allows classifying destructions by their source of origin – technological, economic, social or informational – and determining the nature of the relationships between them.